HUBUNGAN GENETIK DAN PSIKOLOGIS DENGAN KEJADIAN DEPRESI PADA REMAJA - Lidya Isnaini Nuriyah Lidya; Ayik Mirayanti Mandagi; Xindy Imey Pratiwi (Journal of Community Mental Health and Public Policy)
ABSTRACT Depression is one of the most common types of mental disorders that can negatively affect a person's feelings, ways of thinking, and acting so that severe ones can lead to suicide. Depression's caused by various factors, which are genetic and psychological. This study was conducted to determine the relationship between genetic (gender and genetic history) and psychological (social support and psychosocial conditions) with the incidence of depression in adolescents (case study of XY High School students, Jember Regency). This research is an analytic observational study with a cross-sectional method. The sample in this study was 158 respondents who were taken using the simple random sampling method. Data were collected online with the Social Provisions Scale (SPS), Youth Pediatric Symptom-17 (Y PSC-17), and Beck Depression Inventory-II (BDI-II) instruments. The research data were analyzed using the Spearman Correlation Test. The results showed that there was no relationship between genetics which consisted of gender variable (p value = 0.958) and heredity history variable (p value = 0.061) with the incidence of depression in adolescents. While there is a relationship between psychology which consists of social support variables (p value = 0.003) and psychosocial condition variables (p value = 0.000) with the incidence of depression in adolescents. The results of this study can be used as a basis for making preventive, promotive, and rehabilitative efforts regarding depression in adolescents and for further research. Keywords: Depression, Genetic, Psychological, Adolescents.